2022
DOI: 10.3390/jof8050439
|View full text |Cite
|
Sign up to set email alerts
|

Biological Synthesis of Monodisperse Uniform-Size Silver Nanoparticles (AgNPs) by Fungal Cell-Free Extracts at Elevated Temperature and pH

Abstract: Fungi’s ability to convert organic materials into bioactive products offers environmentally friendly solutions for diverse industries. In the nanotechnology field, fungi metabolites have been explored for green nanoparticle synthesis. Silver nanoparticle (AgNP) research has grown rapidly over recent years mainly due to the enhanced optical, antimicrobial and anticancer properties of AgNPs, which make them extremely useful in the biomedicine and biotechnology field. However, the biological synthesis mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Since the XRD analyses, which will be described later, have shown that AgNPs synthesized in the presence of NaCl contain AgCl crystals, we can guess that these were nucleating the AgNPs. In the literature, a wide range of synthesis rates for silver nanoparticles has been reported depending on the biological material used or the synthesis method and conditions, such as pH [ 50 ], temperature [ 29 , 50 ], or NaCl presence [ 29 , 49 ]. In previous work by our group [ 29 ], the presence of NaCl did not speed up AgNP synthesis; the contrary was true.…”
Section: Resultsmentioning
confidence: 99%
“…Since the XRD analyses, which will be described later, have shown that AgNPs synthesized in the presence of NaCl contain AgCl crystals, we can guess that these were nucleating the AgNPs. In the literature, a wide range of synthesis rates for silver nanoparticles has been reported depending on the biological material used or the synthesis method and conditions, such as pH [ 50 ], temperature [ 29 , 50 ], or NaCl presence [ 29 , 49 ]. In previous work by our group [ 29 ], the presence of NaCl did not speed up AgNP synthesis; the contrary was true.…”
Section: Resultsmentioning
confidence: 99%
“…The AgNP synthesis activity level of the C. thermophilum cell-free extract was tested following the study by Alves and Murray [ 3 ]. Briefly, the cell-free extract was heated for 15 min at 90 °C; then, 127.40 mg/L silver nitrate (AgNO 3 , Sigma-Aldrich, St. Louis, MO, USA) was added for a total volume of 500 μL, and heating was continued for one hour at 90 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting AgNPs were characterised based following the study by Alves and Murray [ 3 ]. Ultraviolet–visible spectrophotometry (UV-Vis, BioTek Synergy 4 Microplate Reader, Bad Friedrichshall, Germany) was first used to measure the localised surface plasmon resonance (LSPR) absorbance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that metals like gold, silver, titanium, platinum, selenium, palladium and silica can be utilized for the fabrication of nanoparticles ( Gholami-Shabani et al, 2016 ). Silver nanoparticles (AgNPs) synthesized from F. oxysporum are different in features from those synthesized with Aspergillus fumigates ( Alves and Murray, 2022 ). Studies have reported the synthesis of AgNPs using Coriolus versicolor and Trichoderma reesei ( Vahabi et al, 2011 ; Deniz et al, 2019 ).…”
Section: Fungi Mediated Nano-bioremediationmentioning
confidence: 99%